Improved Digital Image Correlation method. (December 2016) - Mudassar, Asloob Ahmad; Butt, Saira
Abstract: Digital Image Correlation (DIC) is a powerful technique which is used to correlate two image segments to determine the similarity between them. A correlation image is formed which gives a peak known as correlation peak. If the two image segments are identical the peak is known as auto-correlation peak otherwise it is known as cross correlation peak. The location of the peak in a correlation image gives the relative displacement between the two image segments. Use of DIC for in-plane displacement and deformation measurements in Electronic Speckle Photography (ESP) is well known. In ESP two speckle images are correlated using DIC and relative displacement is measured. We are presenting background review of ESP and disclosing a technique based on DIC for improved relative measurements which we regard as the improved DIC method. Simulation and experimental results reveal that the proposed improved-DIC method is superior to the conventional DIC method in two aspects, in resolution and in the availability of reference position in displacement measurements. Highlights: Literature review on Electronic Speckle Photography has been provided. Improved Digital Image Correlation (DIC) technique has been presented and compared with conventional DIC. The technique has been demonstrated with two sets of simulation: one set uses ordinary photographs while the other set uses speckle images. One set of experimental data for concept validation has been included. Through speckle images, in-plane measurement has been demonstrated. It has been established that the proposed technique gives improved results.